Treatment of Skeletal Class III With Extraction And Standard Edgewise: Case Report - Pawinru, Ardiansyah S. (Hasanuddin University, 2021)
Objective: This study was determining the skeletal, dental, and soft tissues changes is respons to camoflage Class III treatment.Methods: A male patient 14 years, 10 months with malocclusion of dental Class I and skelettal Class III, included crowding and crossbite anterior, overbite 3 mm, overjet -1,5 mm, maxillary midline shift to the right 2 mm and mandibular midline shift 1 mm. Treatment was extraction of maxillary and mandibular first premolar with standard edgewise appliance and retention of hawley retainer. After of treatment, correction of the crowding, crossbite anterior and midline, with dental relation class I, normal overbite and overjet is 2 mm.Results: This case is Angle’s class I malocclusion where sagittal interarch relationship is normal, it is preferable to extract in both the arches in order to maintain the interarch relationship, so was that extraction of the right first premolar of maxilla and mandibular.Conclusion: Careful management of the extraction space preserved normal lip support and facial profiles